Capecitabine-induced ventricular fibrillation arrest: Possible Kounis syndrome. (April 2016) - Kido, Kazuhiko; Adams, Val R; Morehead, Richard S; Flannery, Alexander H
We report the case of capecitabine-induced ventricular fibrillation arrest, possibly secondary to type I Kounis syndrome. A 47-year-old man with a history of T3N1 moderately differentiated adenocarcinoma of the colon, status-post sigmoid resection, was started on adjuvant capecitabine approximately five months prior to presentation of cardiac arrest secondary to ventricular fibrillation. An electrocardiogram (EKG) revealed ST segment elevation on the lateral leads and the patient was taken emergently to the cardiac catheterization laboratory. The catheterization revealed no angiographically significant stenosis and coronary artery disease was ruled out. After ruling out other causes of cardiac arrest, the working diagnosis was capecitabine-induced ventricular fibrillation arrest. As such, an inflammatory work up was sent to evaluate for the possibility of a capecitabine hypersensitivity, or Kounis syndrome, and is the first documented report in the literature to do so when evaluating Kounis syndrome. Immunoglobulin E (IgE), tryptase, and C-reactive protein were normal but histamine, interleukin (IL)-6, and IL-10 were elevated. Histamine elevation supports the suspicion that our patient had type I Kounis syndrome. Naranjo adverse drug reaction probability scale indicates a probable adverse effect due to capecitabine with seven points. A case of capecitabine-induced ventricular fibrillation arrest is reported, with a potential for type 1 Kounis syndrome as an underlying pathology supported by immunologic work up.